RoboDiff: combining a sample changer and goniometer for highly automated macromolecular crystallography experiments. Issue 8 (4th August 2016) - Nurizzo, Didier; Bowler, Matthew W.; Caserotto, Hugo; Dobias, Fabien; Giraud, Thierry; Surr, John; Guichard, Nicolas; Papp, Gergely; Guijarro, Matias; Mueller-Dieckmann, Christoph; Flot, David; McSweeney, Sean; et al.
Abstract : An industrial six‐axis robot has been combined with a high‐accuracy air‐bearing rotation axis to create a single device with the capabilities of both transferring cryocooled protein crystals from a sample‐containing dewar and collecting complete X‐ray diffraction data sets. Abstract : Automation of the mounting of cryocooled samples is now a feature of the majority of beamlines dedicated to macromolecular crystallography (MX). Robotic sample changers have been developed over many years, with the latest designs increasing capacity, reliability and speed. Here, the development of a new sample changer deployed at the ESRF beamline MASSIF‐1 (ID30A‐1), based on an industrial six‐axis robot, is described. The device, named RoboDiff, includes a high‐capacity dewar, acts as both a sample changer and a high‐accuracy goniometer, and has been designed for completely unattended sample mounting and diffraction data collection. This aim has been achieved using a high level of diagnostics at all steps of the process from mounting and characterization to data collection. The RoboDiff has been in service on the fully automated endstation MASSIF‐1 at the ESRF since September 2014 and, at the time of writing, has processed more than 20 000 samples completely automatically.